Motion Graphics Branding Video for Increasing Audience Engagement at Zahira Media Publisher Using R&D Method - Putri Oktavianingsih; Purwadi Purwadi (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
The development of social media encourages companies to utilize more engaging and interactive digital communication media to increase audience engagement. Zahira Media Publisher has used video-based promotional media, but has not yet utilized motion graphics optimally, resulting in relatively low audience interaction. This study aims to develop a motion graphics-based branding video and analyze its effectiveness in increasing audience engagement on Instagram. The method used is Research and Development (RD) with a Waterfall model that includes needs analysis, design, implementation, validation, testing, and evaluation. The branding video was developed using Canva and CapCut by applying the AIDA (Attention, Interest, Desire, Action) concept, then validated by media experts and subject matter experts before being published via Instagram Reels. Testing was conducted for seven days using indicators likes, comments, shares, views, and reach. The results showed an increase in all engagement indicators: likes from 13 to 173, comments from 0 to 109, shares from 4 to 31, views from 635 to 1,384, and reach from 398 to 676. Engagement rates also increased from 4.27% to 46.30%. These results indicate that motion graphics-based branding videos effectively increase audience engagement, encourage user interaction, and expand the reach of information through Instagram Reels.